Tingkat kecukupan karbohidrat, lemak, protein dan kaitannya dengan indeks massa tubuh mahasiswa pada hari aktif kuliah - Rendra Kusuma; Taufik Rahman (Physical Education Departement of University PGRI Jombang, 2026)
Nowadays, there are increasing numbers of cases of overnutrition and undernutrition among students. This research is designed to evaluate the adequacy of macronutrient intake among students and their body mass index, and to explore the relationship between these two factors. The design of this research is a cross-sectional study with quantitative methods. The sample in this research was taken purposively, totaling 32 students. A food record questionnaire was utilized over two days to gather information on age, gender, and food consumption. Body weight was measured using a weighing scale, while height was measured using a microtoise. Descriptive analysis presents data on intake frequency, average intake, intake standard deviation, and adequate levels of carbohydrates, protein, fat, and body mass index (BMI). Spearman's rank was used to determine the relationship between adequate levels of carbohydrates, protein, and fat levels and the BMI of Physical Education, Health, and Recreation students. The average carbohydrate intake was 144.4 g, protein 45 g, and fat 42.9 g. The average BMI is 22.6. A significant relationship exists between protein adequacy level and BMI among Physical Education students (p<0.05). There is a significant relationship between the level of fat sufficiency and students' BMI (p<0.05). Meanwhile, the relationship between carbohydrate intake and students' BMI remains unclear. Many students experience a deficiency in macronutrient intake despite having a normal BMI.